MENINGKATKAN KETERAMPILAN PROSES SAINS DAN KARAKTER WASAKA MENGGUNAKAN MODEL PROBLEM BASED LERANING, TEAM ASSISTED INDIVIDUALIZATION DAN MEDIA AUDIO VISUAL PADA MUATAN IPA SISWA KELAS V SDN TELAWANG 4 BANJARMASIN - Vicky Hernandarias; Muhsinah Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem in this study is where during science learning students tend to be passive and do not want to ask questions.and when the teacher asks questions to students, they only answer the questions with answers that are already listed in the book. The question with the answers already listed in the book. To follow up on these problems, the researchers tried to provide a solution to the problem, namely by using a combination of learning model which consists of Problem Based Learning, Team Assisted Individualization and audio visual media. Individualization and audio visual media. The approach used in this research is qualitative research qualitative research and this type of research applies class action research. Type of data presented in this study are qualitative data and quantitative data. Quantitative data. Qualitative data in the form of data on teacher activities and student activities activities in the teaching and learning process, through observation with an observation sheet. observation sheet. Quantitative data in the form of student learning outcomes obtained through written tests at the end of each meeting. This research was conducted at SDN Telawang 4 in the even semester of class V in the 2023/2024 academic year. After conducting 4 meetings with 2 cycles, the results showed that activities of teachers, students, Science process skills, WASAKA character and learning outcomes improved in each cycle with learning outcomes increased in each cycle with the categories of "Very Active", "Highly Skilled" and "Completed". This proves that learning using model of Problem Based Learning, Team Assisted Individualization and audio-visual media is declared successful.audio-visual media was declared successful.